Missense Mutation R338W in ARHGEF9 in a Family with X-linked Intellectual Disability with Variable Macrocephaly and Macro-Orchidism - Long, Philip; May, Melanie M.; James, Victoria M.; Grannò, Simone; Johnson, John P.; Tarpey, Patrick; Stevenson, Roger E.; Harvey, Kirsten; Schwartz, Charles E.; Harvey, Robert J. (Frontiers in Molecular Neuroscience, 2016)
Non-syndromal X-linked intellectual disability (NS-XLID) represents a broad group of clinical disorders in which ID is the only clinically consistent manifestation. Although in many cases either chromosomal linkage data or knowledge of the >100 existing XLID genes has assisted mutation discovery, the underlying cause of disease remains unresolved in many families. We report the resolution of a large family (K8010) with NS-XLID, with variable macrocephaly and macro-orchidism. Although a previous linkage study had mapped the locus to Xq12-q21, this region contained too many candidate genes to be analyzed using conventional approaches. However, X-chromosome exome sequencing, bioinformatics analysis and segregation analysis revealed a novel missense mutation (c.1012C>T; p.R338W) in ARHGEF9. This gene encodes collybistin, a neuronal GDP-GTP exchange factor previously implicated in several cases of XLID, as well as clustering of gephyrin and GABAA receptors at inhibitory synapses. Molecular modeling of the collybistin R338W substitution revealed that this change results in the substitution of a long electropositive side-chain with a large non-charged hydrophobic side-chain. The R338W change is predicted to result in clashes with adjacent amino acids (K363 and D335) and disruption of electrostatic potential and local folding of the PH domain, which is known to bind phosphatidylinositol-3-phosphate (PI3P/PtdIns-3-P). Consistent with this finding, functional assays revealed that recombinant collybistin CB2SH3-R338W was deficient in PI3P binding and was not able to translocate EGFP-gephyrin to submembrane microaggregates in an in vitro clustering assay. Taken together, these results suggest that the R338W mutation in ARHGEF9 is the underlying cause of NS-XLID in this family.